2004
DOI: 10.1098/rspb.2004.2893
|View full text |Cite
|
Sign up to set email alerts
|

Automimicry destabilizes aposematism: predator sample-and-reject behaviour may provide a solution

Abstract: Aposematism, the use of conspicuous colours to advertise unpalatability to predators, is perhaps the most studied signalling system in nature. However, its evolutionary stability remains paradoxical. The paradox is illustrated by the problem of automimicry. Automimics are palatable individuals within a population of unpalatable aposematics. Automimics benefit from predators avoiding warning coloration without carrying the models' cost of unpalatability, and should increase in the population, destabilizing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 31 publications
5
63
2
Order By: Relevance
“…Published work uses young domesticated chickens (Gamberale-Stille and Guilford 2004;Skelhorn and Rowe 2007) whose feeding behaviour is rather different from most passerine birds. For example, chicks learn to find food items by pecking and tasting everything from non-organic objects to organic items.…”
Section: Experiment: Quantifying Individual and Public Goods From Chementioning
confidence: 99%
See 2 more Smart Citations
“…Published work uses young domesticated chickens (Gamberale-Stille and Guilford 2004;Skelhorn and Rowe 2007) whose feeding behaviour is rather different from most passerine birds. For example, chicks learn to find food items by pecking and tasting everything from non-organic objects to organic items.…”
Section: Experiment: Quantifying Individual and Public Goods From Chementioning
confidence: 99%
“…Daly et al (2012a) for example showed that frequency of nondefended prey increased with group size in caterpillars of the large white butterfly (Pieris brassicae). Such non-defended individuals might be considered parasitic cheats if their presence in a population of defended prey has a consequence of raising the attack rates as indicated in several recent experiments (Gamberale-Stille and Guilford 2004;Skelhorn and Rowe 2007;Jones et al 2013). These cheats are often known as ''automimics'' .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent laboratory experiments have shown that birds can taste the difference between defended and undefended prey in both aposematic and cryptic populations (Skelhorn & Rowe 2006b;Halpin et al 2008a,b). However, if birds can accurately taste-reject prey that invest in different levels of toxins (Gamberale-Stille & Guilford 2004;Skelhorn & Rowe 2005), this leaves a different problem of trying to explain the widespread existence of variation in toxicity in prey populations (e.g. Brower et al 1967;.…”
Section: Introductionmentioning
confidence: 99%
“…Hence key questions of current importance in aposematism theory focus on the question: how conspicuous should a signal be, and how much should be invested into secondary defences [16,25,29,30]? Moreover, which factors influence evolutionary stability of honest signalling and what is the role of mimics in maintaining or destabilising aposematic display [10]? To explain stability and persistence of aposematic signals we require a theory of co-evolution of defence and signals [27,38].…”
Section: Introductionmentioning
confidence: 99%